Herpes Simplex Virus Methods and Protocols - Diefenbach, Russell J.; Fraefel, Cornel; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
Herpes Simplex Virus: Methods and Protocols provides a wide collection of protocols employed in various levels of herpes virus research, including basic protocols on growing viruses in cell culture and cloning, manipulating, and preparing viral DNA. Other chapters describe approaches to design and apply HSV-1 vectors for vaccination, cancer and gene therapy, or to study specific aspects of HSV-1 biology such as latency, intracellular transport, and protein-protein interaction. Procedures for structural analyses, microscopy, proteomics, and testing of antivirals are included as well.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Practical and authoritative, Herpes Simplex Virus: Methods and Protocols will aid new researchers in the field of herpes virology as well as those experienced investigators wishing to embark on new techniques.
HSV-1 Biology and Life Cycle -- Herpes Simplex Virus Growth, Preparation, and Assay -- Isolation of Herpes Simplex Virus Nucleocapsid DNA -- Construction and Characterization of Bacterial Artificial Chromosomes (BACs) Containing Herpes Simplex Virus Full-Length Genomes -- Engineering HSV-1 Vectors for Gene Therapy -- Herpes Simplex Virus Type 1 (HSV-1)-Derived Amplicon Vectors -- HSV-1 Amplicon Vectors as Genetic Vaccines -- Modification of HSV-1 to an Oncolytic Virus -- Herpes Simplex Virus Mutant Generation and Dual Detection Methods for Gaining Insight into Latent/Lytic Cycles In Vivo -- Phenotypic and Genotypic Testing of HSV-1 Resistance to Antivirals -- Using Homogeneous Primary Neuron Cultures to Study Fundamental Aspects of HSV-1 Latency and Reactivation -- Characterization of Extracellular HSV-1 Virions by Proteomics -- A Precipitation-Based Assay to Analyze Interactions of Viral Particles with Cytosolic Host Factors -- Affinity Purification Combined with Mass Spectrometry to Identify Herpes Simplex Virus Protein-Protein Interactions -- Preparation of Herpes Simplex Virus Infected Primary Neurons for Transmission Electron Microscopy -- Multifluorescence Live Analysis of Herpes Simplex Virus Type-1 Replication -- Expression, Purification and Crystallization of HSV-1 Glycoproteins for Structure Determination -- Cryo-EM Techniques to Resolve the Structure of HSV-1 Capsid-Associated Components -- In Vivo HSV-1 DNA Transport Studies Using Murine Retinal Ganglion Cells -- HSV-1 Protein Expression Using Recombinant Baculoviruses -- The Murine Intravaginal HSV-2 Challenge Model for Investigation of DNA Vaccines.
Keywords: Infectious diseases; Virology; Infectious Diseases; Virology